Efektivitas Media Leaflet terhadap Pengetahuan Penggunaan Obat Antihipertensi di Puskesmas Melintang: Effectiveness of Leaflet Media on Knowledge of Antihypertensive Drug Use at the Melintang Health Center - Rachmawat Felani Djuria; Aprilia Nurjanah; Lana Sari; Dela Lanaya (Poltekes Kemenkes Tanjungpinang, 2023)
The prevalence of hypertension in Indonesia increased to 34.1% at the age of ≥18 years. Puskesmas Melintang ranked the first highest number of hypertension cases among other health centers in Pangkalpinang City with 3,694 cases in 2019. The study was conducted to determine the effectiveness of leaflet media in improving the knowledge of the rational use of antihypertensive drugs in the working area of Puskesmas Melintang. The method used was quantitative analytic experimental research with a one-group pretest-posttest design. Data collection in the study was using a non-random sampling method with an accidental sampling technique. The number of samples in this study was 67 respondents. The measuring instrument used in the study was a questionnaire given to the community who became the sample in two pre-test and post-test measurements using leaflet media analyzed by univariate and bivariate analysis tests. The results showed that there was a significant difference in the value of knowledge changes before and after giving leaflet media on the use of antihypertensive drugs with a p-value of 0.000 <0.05. Puskesmas officers provide continuous and scheduled counseling or socialization activities on the rational use of antihypertensive drugs to the community using leaflet media or other information media.